Airport Expansion and the British Planning System: Regime Management. Issue 3 (6th June 2018) - Marshall, Tim
Abstract: The article examines the process whereby government and business elites have driven the expansion of London airports, particularly via the mode of the establishment of an 'independent' commission, the Davies Commission (2012–2015). It addresses the strategic framing of airports planning, including the role of National Policy Statements, and the nature of the consideration of the planning applications for consent to develop. Temporal and geographical dimensions are analysed, showing how central to the UK state project is the expansion of the southern English / Greater London core, with associated infrastructure geographies. It concludes that corporate and state power may well achieve the desired expansion of airport capacity in the London region, overriding environmental and other non‐commercial considerations. However, there are tensions in the dominant state and business model, given an apparent commitment to carbon emissions reduction and other air quality goals, as well as to minimising the costs to the public sector which airport expansion is likely to generate.